STRATEGI MANAJEMEN PERUBAHAN DALAM TRANSFORMASI DIGITAL DI PERUSAHAAN FUJIFILM - Widhia, Danendra Amantha; Handayani, Devyasri Nusa; Sri, Dewi; Gani, Fauzan Putra; Sayyidan, Radya Maysar (Bussman Journal : Indonesian Journal of Business and Management, 2024)
Change management applied by fujifim in the face of digital transformation which as a company originally engaged in the analogue photography industry, fujifilm has succeeded by making fundamental changes to not change or survive in the digital era. This research uses a qualitative method with a literature review approach. Fujifilm found success that lies in the vision of strong leadership and organised or structured management and can take advantage of opportunities towards digital as creating new value. In conducting the analysis, the STPD (See, Think, Plan, Do) model can be used to identify change management opportunities. This study shows that the success of digital transformation of Fujifilm does not only depend on technology alone, but there are human resources and effective communication as overcoming opposition to change management